Blood thyroid hormones, insulin and leptin, metabolites and enzymes in transition dairy ewes, as affected by dietary linseed and physiological stage. (10th December 2022) - Todini, Luca; Malfatti, Alessandro; Mughetti, Laura; Acuti, Gabriele; Barbato, Olimpia; Beghelli, Daniela; Trabalza-Marinucci, Massimo
Abstract: This study investigated the effects of dietary linseed and physiological state on blood concentrations of some metabolic hormones and indicators, in transition dairy ewes. From 21 d before lambing to 60 d post-partum, ewes were provided with one of three isoenergetic and iso‑nitrogenous pelleted concentrates, without (CTR, n = 21), or with 100 (EL-10, n = 22) or 200 g/kg (EL-20, n = 22) of extruded linseed. Animals were fed alfalfa hay ad libitum and had access to mixed pasture. Plasma thyroid hormones and insulin concentrations were not affected by diet and significantly changed by time. The last week of pregnancy T3 (2.27 ± 0.15 ng/mL) and T4 (102.63 ± 2.85 ng/mL) were lower than at 4 weeks before lambing (T3: 3.27 ± 0.27 ng/mL; T4: 125.89 ± 2.63 ng/mL). After lambing, T3 rose to be highest at 4 and 8 weeks of lactation (3.41 ± 0.22). Mean insulin peaked 2 weeks after lambing (0.31 ± 0.02 ng/mL) vs. late pregnancy (0.22 ± 0.01 ng/mL) and progressing lactation (0.18 ± 0.01 ng/mL). Plasma Leptin concentration (2.43 ± 0.03 ng/mL) was not affected by diet nor time. All the blood metabolites and enzymes investigated showed significant time x treatment interaction. Differences of several haematological parameters were found in EL vs. CTR (cholesterol, triglycerides, total protein, bilirubin, ALP, ALT), however, in most cases the values were fairly within the reference physiological ranges. Metabolic hormones are confirmed to be mainly linked to the different physiological states, energy intake and variations of energy balance, without clear effects by different sources of energy and quality of dietary lipids. Highlights: Milk and cheese nutritional properties are improven by dietary Omega-3 Fatty Acids. Linseed is rich in Omega-3 Fatty Acids. Linseed rich diets affected blood metabolites in dairy ewes. Linseed rich diets did not affect metabolic hormones in blood. Metabolic hormones are mainly linked to energy balance rather than to lipid sources.